Assessment of Heavy Metal Concentration in Soil and Water from Mechanic Sites in Makurdi, Benue State, Nigeria - Mark-Victor, Idakwo Abutu; Emmanuel, Tembe T.; Thomas, Okoh (Journal of Environment Sciences, 2025)
This study assessed heavy metal concentrations and physicochemical properties in soil and water samples from mechanic workshops in Apir and North Bank, Makurdi, Nigeria. sixteen soils, sixteen water samples were collected using a systematic random sampling design, along with control samples from uncontaminated sites. Soil samples were collected from depth of 15 cm using a hand auger and stored in labeled polyethylene bags, while water samples were collected in clean plastic bottles and taken to the laboratory. The physicochemical properties analyzed included pH, moisture content, cation exchange capacity (CEC), electrical conductivity (EC), and total dissolved solids (TDS), measured using standard laboratory procedures. Heavy metal concentrations of manganese (Mn), lead (Pb), iron (Fe), and chromium (Cr) were determined using atomic absorption spectrophotometry (AAS) after acid digestion. The results showed that North Bank soils had higher manganese levels (1.24 mg/kg) compared to Apir (0.28 mg/kg), while Apir exhibited elevated concentrations of lead (3.14 mg/kg) and chromium (1.04 mg/kg) compared to North Bank (Pb: 2.78 mg/kg, Cr: 0.57 mg/kg). However, all heavy metal concentrations were below the NESREA (National Environmental Standards and Regulations Enforcement Agency) permissible limits. Soil pH values were 7.2 for North Bank and 6.9 for Apir, both within the acceptable NESREA range (6.5–8.5). Moisture content and CEC were higher in North Bank and Apir, respectively. Water samples contained no detectable levels of manganese, lead, or chromium, and their physicochemical properties, including pH, EC, and TDS, were within safe limits. The findings suggest that soil contamination remains within regulatory thresholds, necessitating continuous monitoring and improved waste management practices.